Mobile phone graphical user interface (GUI) for appliance remote control: An SMS-based electronic appliance monitoring and control system - Africa, Aaron Don M. (Animo Repository, 2019)
The home monitoring system is an effective way to prevent many household accidents that may occur whether we are aware or not. There are a lot of home control devices which were developed in the past. Take fire hazards for example, there are a lot of ways for a house fire to occur like overheating appliances. Fire imposes a big hazard in our homes but there is a device that was built to lessen the probability of this from occurring or at least lessen the damage done. The fire alarm works whenever there is enough smoke that goes in the detector. It will automatically make a sound to alarm the people inside the house, some home systems have a built-in sprinkler that work when the fire alarm activates preventing further property destruction. There are a lot of ways of designing a home control system but at these times, the design must be adaptable and adaptive to most people. Global System for Mobile Communication (GSM) is a means of wireless communication between people. It can also be used to communicate with devices such that it functions even if a user is not physically present in the vicinity of the device. GSM is the most adaptable medium since it has a further range of communication compared to Bluetooth and infrared. Moreover, it is also more accessible than Wi-Fi since it is more widely available. A home monitoring system interfaced with GSM poses a great advantage and convenience to the public. The user can be updated regarding the status (ON or OFF) of his appliances which can prevent future damage. It will also be able to alarm the user of any irregular activities of the appliances immediately even if the user is at another place. © 2019, World Academy of Research in Science and Engineering. All rights reserved.